The The Impact of ESG Transparency on the Financial Performance of Companies Listed in the LQ45 Index: An Empirical Study (2022–2024) - Griselda Livia; Merry Susanti (Golden Ratio of Data in Summary, 2026)
This study aims to provide empirical evidence on the effect of Environmental, Social, and Governance (ESG) disclosure on financial performance. The study uses 60 firm-year observations from 20 companies included in the LQ45 Index and listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The sampling technique employed is purposive sampling. Hypothesis testing is conducted using multiple linear regression analysis. The Random Effect Model (REM) is applied to estimate the Return on Assets (ROA) model, while the Fixed Effect Model (FEM) is used to estimate the Return on Equity (ROE) model. Data are processed using EViews 13. Financial performance is measured using Return on Assets (ROA) and Return on Equity (ROE). The results indicate that Environmental, Social, and Governance disclosures do not have a significant effect on financial performance. These findings are expected to provide valuable insights for regulators, investors, and corporate management in developing and implementing ESG frameworks to enhance financial performance.